2019
DOI: 10.1039/c8cc09573f
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of the perovskite series La1−xSrxCoO3−δ during chemical looping with methane

Abstract: Perovskite oxides are promising materials as oxygen carriers in chemical looping applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…NiO, Fe 2 O 3 , CeO 2 , spinel and certain perovskitebased oxides possess suitable thermodynamic properties that permit their use as redox catalysts for chemical looping conversion of CH 4 to synthesis gas. 41,[179][180][181][182][183][184] Among various oxygen carriers, Ni-based oxygen carriers are particularly attractive for CLR owing to their high catalytic activity for CH 4 reforming. 56,[185][186][187][188][189][190][191] NiO possesses a low selectivity towards synthesis gas, but as NiO reduces to Ni the selectivity towards synthesis gas increases.…”
Section: Perspectivementioning
confidence: 99%
“…NiO, Fe 2 O 3 , CeO 2 , spinel and certain perovskitebased oxides possess suitable thermodynamic properties that permit their use as redox catalysts for chemical looping conversion of CH 4 to synthesis gas. 41,[179][180][181][182][183][184] Among various oxygen carriers, Ni-based oxygen carriers are particularly attractive for CLR owing to their high catalytic activity for CH 4 reforming. 56,[185][186][187][188][189][190][191] NiO possesses a low selectivity towards synthesis gas, but as NiO reduces to Ni the selectivity towards synthesis gas increases.…”
Section: Perspectivementioning
confidence: 99%
“…Usually even the most promising materials in the literature applied for CL show an initial drop in activity and change in the selectivity over the rst 10-20 cycles before stabilising (or further decline) or require much higher temperature to achieve similar conversions. 45,46 Here we show that it is possible to have a material that maintains its initial performance over multiple cycles. In addition, there is no carbon deposition present throughout the duration of the experiment (Fig.…”
Section: Application and Long-term Durabilitymentioning
confidence: 76%
“…By the means of in situ synchrotron Xray powder diffraction (SXRD), the cycling stability and structural evolution of perovskite oxides (La 1−x Sr x CoO 3−δ ) during chemical looping have been reported and discussed. 44 Via in situ Raman, a highly reactive chemical reaction interface consisting of lattice oxygen and the corresponding metal atoms that are always present on the oxygen carrier surface has been confirmed. 45 Miller et al 35 observed the formation of calcium ferrite phases during methane reduction that occurs in the sequence CaFe 2 O 4 → CaFe 3 O 5 + Ca 2 Fe 2 O 5 → FeO + Fe + CaO → Fe + CaO via in situ X-ray diffraction (XRD).…”
Section: In Situ Characterizationmentioning
confidence: 87%
“…For instance, via in situ X-ray photoelectron spectroscopy (XPS), an important hydroxyl ion formation process on the surface of OCs during chemical looping reactions has been directly captured. By the means of in situ synchrotron X-ray powder diffraction (SXRD), the cycling stability and structural evolution of perovskite oxides (La 1– x Sr x CoO 3−δ ) during chemical looping have been reported and discussed . Via in situ Raman, a highly reactive chemical reaction interface consisting of lattice oxygen and the corresponding metal atoms that are always present on the oxygen carrier surface has been confirmed .…”
Section: Advanced Technology For Exploring the Chemical Looping React...mentioning
confidence: 99%
See 1 more Smart Citation